Analysis of leaf flavonoid composition of some Iranian Cotoneaster Medik. (Rosaceae) species - Zeynab Lotfi; Fahimeh Salimpour; Fariba Sharifnia; Sedigheh Arbabian; Maryam Peyvandi (Acta Biologica Sibirica, 2019)
The genus Cotoneaster consists of unarmed shrubs that naturally distributed in north parts of Iran. It is a problematic genus, and there are many discussions about its species number in Iran as well the World. Recently, M Khatamsaz has been listed 19 species of it in Iran. In the current research, we studied leaf flavonoid composition of seven Cotoneaster species from Iran. These species were harvested from the northern provinces of the country and their leaf ethanolic extracts were subjected to HPLC, for detection the types and amounts of their flavonoid compounds. We identified four flavonoid compounds: rutin, myricetin, quercetin, and kaempferol. The concentration of these flavonoids differed between the species, moreover amount of each flavonoid also varied among the studied species. All of them were registered in the studied species, except for myricetin, which was not observed in C. nummularius. The highest amount of flavonoids were detected in C. nummularius, while C. discolor had the lowest one. The evaluated species divided into four distinct group in UPGMA tree. According to CA-Joined plot, each group was characterized by species amount of flavonoid(s). All of evaluated species belonged to the same section of the genus, therefore our findings revealed that the flavonoid data were useful at sectional level for identification of the species.